A content analysis on top risks in social networking - Sakgasit Ramingwong (2018)
© Springer Science+Business Media Singapore 2016. The emergence of social networking during the recent years is phenomenon. Indeed, social networking offer a number of benefits to users. Yet, inevitably, this technology is vulnerable to risks. It is important for social networking stakeholders to realize potential risks in order to plan for mitigation efficiently. This paper investigates and summarizes risks described in recent literature. The result can be used as a guideline for risk identification for social networking related scenario.